Effects and safety of delayed versus early umbilical cord clamping in newborns of HIV-infected mothers. (16th February 2019) - Pogliani, L.; Erba, P.; Nannini, P.; Giacomet, V.; Zuccotti, G. V.
Abstract: Objective: To investigate the effect of a 2 minutes-delayed cord clamp (DCC) versus early cord clamp (ECC) on neonate haemoglobin concentration 24 hours and 1 month after birth, and assess the safety of DCC concerning the risk of HIV infection. Design: Sixty-four mother-infant peers were enrolled. All mothers were on stable ARV therapy. Viral load, CD4 + count and blood haemoglobin (Hb) concentrations 24 hours before delivery were collected from all mothers and their infants. Methods: All patients were enrolled at the Department of Paediatrics, AO FBF Sacco Hospital in Milan, and were followed until 18 months after birth. Women with haematological diseases and obstetrical complications were excluded. All of 64 mother and infants couples (32 ECC group and 32 DCC group) completed the study. ECC and DCC are defined as application of umbilical clamp within 30 seconds and 120 seconds after birth, respectively. Results: Mean birth weight was significantly higher in the DCC compared with ECC group. Mean Hb levels at birth were significantly higher in DCC than in ECC group ( p = .05): this difference persisted at 1 month of life. All newborns showed negative viral load. Conclusions: DCC 2 minutes after birth is proven to be a safe procedure, particularly beneficial in newborns from HIV mothers. The risk of anemia is significantly decreased at 24 hours after birth and persists at age of 1 month without any increased risk of neonatal jaundice or polycitemia.